# Is this correct?

P(n): 1 + 3 + 5 + ... + (2n-1) = n^2

Prove P(1)
P(1) = 1 = 1^2
P(1) is true

(A) P(k): 1 + 3 + 5 +...+ (2k-1) = k^2

(B) P(k + 1): 1 + 3 + 5 +...+ (2k-1) + (2(k+1)-1)
or
(2k-1) + (2k + 1) = (k+1)^2

Assuming A, prove B

(2k-1) = k^2
(2(k+1)-1) = (k+1)(k+1)
(2k + 1) = (k^2 + 2k+ 2)
= (k+1)^2

When in comes to the inductive step, does it "differ" from problem to problem? I can always get to the inductive assumption, but then I'm never sure just how to go about proving it.

Related Precalculus Mathematics Homework Help News on Phys.org
HallsofIvy
Homework Helper
P(n): 1 + 3 + 5 + ... + (2n-1) = n^2

Prove P(1)
P(1) = 1 = 1^2
P(1) is true

(A) P(k): 1 + 3 + 5 +...+ (2k-1) = k^2

(B) P(k + 1): 1 + 3 + 5 +...+ (2k-1) + (2(k+1)-1)
or
(2k-1) + (2k + 1) = (k+1)^2
I'm, sorry? how does 1+ 3+ ...+ 2(k+1)= (2k-1)+ 2k???

Assuming A, prove B

(2k-1) = k^2
(2(k+1)-1) = (k+1)(k+1)
(2k + 1) = (k^2 + 2k+ 2)
= (k+1)^2

When in comes to the inductive step, does it "differ" from problem to problem? I can always get to the inductive assumption, but then I'm never sure just how to go about proving it.
You want to prove that "P(k)= (k+1)^2. P(k+1)= P(k)+ 2k+1 for every k. The "induction hypothesis" is that P(k-1)= k^2 . From that, P(k+1)= P(k)+ k+1= k^2+ 2k+ 1= (k+1)^2/